Downlink outage probability analysis of distributed MIMO systems over a composite fading channel - Wen-jie PENG; Yue-heng LI; Mei-yan JU; Ping HUANG; Guo-ping TAN (Tongxin xuebao)
The downlink outage probability of the distributed MIMO systems over a composite channel was discussed. Firstly, a composite fading channel was established by integrating Nakagami-m fading, path loss, and lognormal shad-owing. According to the distributed MIMO system with a center-located base station (BS), a quasi-uniform mobile station (MS) distribution model was proposed, which is more suitable for a real communication environment. Next, an approxi-mate analytical expression of average downlink outage probability of the system with arbitrary MS distribution was de-rived through using mathematical methods such as moment generating function, Gauss-Hermite integral, composite Simpson's rule and so on. Finally, by taking the proposed MS distribution model into account, the derived closed-form outage probability expression and the MS distribution were proved to be correct and reasonable by computer simulation results.